The Lifestyle Of Allied Medical Students Studying At Tehran University Of Medical Sciences In 2012 - Leila Goudarzi; Aslan Nazari; Ghasem Rajabi Vasokolaee; Mohammad Salimi; Mehdi Raadabadi (Tehran University of Medical Sciences, 2014)
Background and Aim: Due to certain problems including being away from their families, entering a large and full-of-tension environment, and having economic problems caused by lack of sufficient income, students are likely to lose their mental health. This study is aimed to investigate college students' conditions and lifestyle at Tehran University of Medical Sciences (TUMS).  Materials and Methods: In this cross-sectional study, 120 students from School of Allied Medicine were selected through simple sampling. Data collection tools included demographic questions and a lifestyle questionnaire. After collecting the questionnaires and coding the questions, the obtained data were analyzed through such statistical tests as t-test and ANOVA using SPSS software version 18.  Results: Students' scores on lifestyle test were in the intermediate range and far from a desired situation. A two-sample t-tests did not show a significant relationship between students' lifestyle and their gender and marital status (P>0.05). Moreover, ANOVA test didn't show a significant relationship between students' age and educational level on the one hand and their lifestyle factor on the other.  Conclusion: The results of the study revealed that students' lifestyle scores were in the intermediate range and that the situation was far from good. Standard educational programs and interventions should be designed to change students' lifestyle. Nutritional and physical support systems and educational, cultural, and entertainment programs in the department of physical education can minimize the concerns and preoccupations of the studied population group.